Understanding Sport-Related Concussion: A Comprehensive Overview - Kałuża, Jessica Adriana; Nowak, Aleksandra; Ledowicz, Agata; Rogoń, Agnieszka; Bednarczyk, Małgorzata; Moskal, Bartosz; Zabojska, Krystyna; Tomaka, Rafał; Szostak, Kamila; Dydyk, Martyna (Quality in Sport, 2024)
This paper provides a comprehensive overview of sport-related concussions, highlighting the critical importance of understanding their mechanisms, diagnosis, and management. Sport-related concussion is a frequent and complex pathology whose physiopathological mechanisms are not completely understood yet. Concussions, a subset of traumatic brain injuries, are prevalent in contact sports and pose significant risks to athletes’ long-term health. The review covers the pathophysiology of concussions, emphasizing the biomechanical forces involved and the resultant neurological disruptions. Athletes seldom report concussive symptoms, which makes the diagnosis a challenge. Therefore, diagnostic challenges are explored, with a focus on clinical assessment tools, neuroimaging, and biomarkers. Additionally, the paper discusses current management strategies, including return-to-play protocols, and the role of education in concussion prevention. The review underscores the need for ongoing research to enhance diagnostic accuracy, improve treatment outcomes, and establish more effective prevention strategies, ultimately aiming to safeguard athletes’ well-being.